Two-dimensional carbazole-based derivatives as versatile chemosensors for colorimetric detection of cyanide and two-photon fluorescence imaging of viscosity in vitro. (February 2017) - Zhang, Wan; Xu, Kaixiang; Yue, Liangxu; Shao, Zonglong; Feng, Yan; Fang, Min
Abstract: A pair of carbazole-based derivatives with two-dimensional chromophore structures was designed and employed for the measurement of cyanide and viscosity, respectively. We investigated the ability of hydrazone derived from 2, 4-dinitrophenylhydrazine to detect CN − by UV–vis spectroscopy involving the NH proton abstraction by cyanide ions. With addition of CN − to the solution of the 2, 4-dinitrophenylhydrazine derived chemosensor, color changes from yellow to violet were observed, accompanied by 60 nm red-shift of the maximum absorption wavelength. Absorbance ratio (A500 /A440 ) of this chemosensor had a good linear relationship with the concentration of CN − ranging from 0 to 30 μM. Meanwhile, the carbazole-based chemosensor containing a 4-nitrophenylhydrazone unit exhibited a "turn on" fluorescence response to changes in viscosity by increasing the viscosity of methanol-polyethyleneglycol system or reducing the temperature of testing environment. The good linear relationships can be found between the logarithmic relations of viscosity and one/two-photon fluorescence intensity. Confocal fluorescence imaging experiments indicated the latter chemosensor could be applied for visualizing viscosity in living cells and fresh liver tissues under the two-photon excitation. Graphical abstract: Highlights: Two-dimensional carbazole-based chemosensorsL1 andL2 were developed. L1 had the high selectivity and sensitivity for the colormetric detection of CN − . L2 can be used as a molecular rotor and had a "turn on" fluorescence response to viscosity. L2 can be applied for visualizing viscosity in vitro under the two-photon excitation.